Fuzzy Sub Implicative Ideals of KU-Algebras - Samy Mohammed Mostafa; Ola Wageeh Baseer (Journal of New Theory, 2018)
We consider the fuzzification of sub-implicative (sub-commutative) ideals in KU-algebras, andinvestigate some related properties. We give conditions for a fuzzy ideal to be a fuzzy sub-implicative (subcommutative)ideal. We show that any fuzzy sub-implicative (sub-commutative) ideal is a fuzzy ideal, butthe converse is not true. Using a level set of a fuzzy set in a KU-algebra; we give a characterization of a fuzzysub-implicative (sub-commutative) ideal.